Analytical Approach for Load Capacity of Large Diameter Bored Piles Using Field Data (Journal of Engineering, 2015)
An analytical approach based on field data was used to determine the strength capacity of large diameter bored type piles. Also the deformations and settlements were evaluated for both vertical and lateral loadings. The analytical predictions are compared to field data obtained from a proto-type test pile used at Tharthar –Tigris canal Bridge. They were found to be with acceptable agreement of 12% deviation.               Following ASTM standards D1143M-07e1,2010, a test schedule of five loading cycles were proposed for vertical loads and series of cyclic loads to simulate horizontal loading .The load test results and analytical data of 1.95m in diameter test pile proved efficiently to carry a working load of 450 tons. The calculated lateral displacements based on a specified coefficient of subgrade reaction are compared to the measured values from dial gauges and strain gauges placed at various locations along the length of the pile.